Facilitating Proton Transport in Nafion-Based Membranes at Low Humidity by Incorporating Multifunctional Graphene Oxide Nanosheets - He, Xueyi; He, Guangwei; Zhao, Anqi; Wang, Fei; Mao, Xunli; Yin, Yongheng; Cao, Li; Zhang, Bei; Wu, Hong; Jiang, Zhongyi (ACS applied materials & interfaces, 2017)
Nafion, as a state-of-the-art solid electrolyte for proton exchange membrane fuel cells (PEMFCs), suffers from drastic decline in proton conductivity with decreasing humidity, which significantly restricts the efficient and stable operation of the fuel cell system. In this study, the proton conductivity of Nafion at low relative humidity (RH) was remarkably enhanced by incorporating multifunctional graphene oxide (GO) nanosheets as multifunctional fillers. Through surface-initiated atom transfer radical polymerization of sulfopropyl methacrylate (SPM) and poly(ethylene glycol) methyl ether methacrylate, the copolymer-grafted GO was synthesized and incorporated into the Nafion matrix, generating efficient paths at the Nafion–GO interface for proton conduction. The Lewis basic oxygen atoms of ethylene oxide (EO) units and sulfonated acid groups of SPM monomers served as additional proton binding and release sites to facilitate the proton hopping through the membrane. Meanwhile, the hygroscopic EO units enhanced the water retention property of the composite membrane, conferring a dramatic increase in proton conductivity under low humidity. With 1 wt % filler loading, the composite membrane displayed the highest proton conductivity of 2.98 × 10–2 S cm–1 at 80 °C and 40% RH, which was 10 times higher than that of recast Nafion. Meanwhile, the Nafion composite exhibited a 135.5% increase in peak power density at 60 °C and 50% RH, indicating its great application potential in PEMFCs.